Changes in Growth Performance, Nutrient Metabolism, Antioxidant Defense and Immune Response After Fishmeal Was Replaced by Low-Gossypol Cottonseed Meal in Golden Pompano (Trachinotus ovatus) - Qin, Yawen; He, Chaoqun; Wang, Wenqiang; Yang, Peng; Wang, Jun; Qin, Qinbo; Mai, Kangsen; Song, Fei (Frontiers in Marine Science, 2021)
Present study was designed to elucidate the changing pattern of growth performance, nutrient metabolism, antioxidant defense and immune response after fishmeal (FM) was replaced by cottonseed meal (CSM). Four isonitrogenous and isolipidic experimental diets (42.5% crude protein, 14.0% crude lipid) were formulated to replace 0% (CSM0 diet), 20% (CSM20 diet), 40% (CSM40 diet) and 60% (CSM0 diet) of the FM protein with CSM. Juvenile golden pompano (Trachinotus ovatus) with an initial body weight of 24.8±0.02 g were fed each diet for 6 weeks. The results showed that compared with the control diet, significant differences were not found in the weight gain ratio, specific growth performance and apparent digestibility of dry matter and protein after 20% FM was replaced by CSM. Higher CSM replacement markedly decreased the growth performance (P<0.05). Moreover, the CSM20 and CSM40 diets did not depress the feed efficiency ratio and protein efficiency ratio compared with the CSM0 diet. Further exploring the physio-biochemical and molecular responses, the present study also showed that dietary 20%-40% CSM replacement had no significant effect on altering the whole body, plasma nutrient contents, free amino acids, or whole-body fatty acid contents. Additionally, the CSM20 diet did not change the mRNA and protein phosphorylation levels of the key enzymes and regulators involved in target of rapamycin (TOR) and amino acid response (AAR) signaling, nutrient metabolism, immune response and antioxidant defense. Higher CSM inclusion significantly varied the TOR and AAR signaling response, nutrient metabolism, immune response and antioxidant defense. Based on the results, CSM could successfully replace 20% FM in the formulated diets for golden pompano. This study proposes the optimal inclusion level of CSM in the diet, which has important significance in optimizing aquafeeds formulation.